Granzyme B-expressing γδ-T and NK cells as a predictor of clinical pregnancy failure in patients with unexplained repeated implantation failure. (April 2021) - Huang, Chunyu; Zhang, Yongnu; Xiang, Zheng; Li, Yuye; Lin, Rong; Xu, Jian; Tu, Wenwei; Zeng, Yong
Highlights: Granzyme B could be a predictor of pregnancy failure in uRIF patients. Four-tier risk model can classify risk level of pregnancy failure of uRIF patients. Both of elevated granzyme B + gd-T cells and decreased granzyme B + NK cells are potential indicators for clinical pregnancy failure. Clinicians can give individualized suggestion to uRIF patients based on the model. Abstract: The limited cytotoxicity of immune cells facilitates a successful establishment of pregnancy. However, the association between cytotoxic granules and unexplained repeated implantation failure (uRIF) remains unkown. Twenty-one fertile controls and 54 patients with uRIF were included in this study. The pregnancy outcomes were monitored at different gestational periods. The peripheral blood lymphocytes were detected using specific monoclonal antibodies by flow cytometry. The percentage of perforin + (Pfr + ), granzyme B + (GrB + ), or granulysin + (Gnly + ) lymphocytes was not significantly different among fertile controls, uRIF patients with successful pregnancy outcomes, and uRIF patients with pregnancy failure. The percentage of GrB + γδ-T cells in lymphocytes was markedly higher in uRIF patients with implantation failure and clinical pregnancy failure than that in uRIF patients with a corresponding successful pregnancy outcome. A four-tier risk model showed that the risk of suffering clinical pregnancy failure in uRIF patients among high risk tier (83.3 %), normal risk tier (65.0 %) and low risk tier (39.1 %) was elevated by 2–4 fold compared with uRIF patients among lowest risk tier (20.0 %). In addition, the percentage of GrB + NK cells in lymphocytes tended to decrease in uRIF patients with pregnancy failure. The AUC of the combined indicator with GrB + γδ-T cells and GrB + NK cells was increased than that of GrB + γδ-T cells and GrB + NK cells for predicting clinical pregnancy failure. In conclusion, the frequency of GrB-expressing γδ-T and NK cells in peripheral blood could serve as a predictor of clinical pregnancy failure in patients with uRIF.